(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
The present study was conducted to clarify the histological effect of ciprofloxacin, on albino mice articular cartilage. The study conducted 30 neonate mice divided into 3 groups, 2 groups were administrated using 100 and 500 mgkg B.W.day for 30 days oral dose of ciprofloxacin. The last group was the control. After that the joint were fixed for histological studies. Histological changes were observed in the joints chondrocyte loss, matrix degeneration, and erosion of the articular cartilage.